Fibrosis biomarkers as a predictive tool for clinical outcome in PLNR14Del patients. (24th May 2021) - Van Der Voorn, SM; Bourfiss, M; Te Riele, ASJM; Taha, K; Vos, MA; Van Veen, TAB
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Netherlands Cardio Vascular Research Initiative (CVON): the Dutch heart foundation Background: Mutations in phospholamban (PLN, most often PLNR14Del), a protein that regulates Ca2+ homeostasis in cardiomyocytes, are found in patients diagnosed with arrhythmogenic (ACM) and dilated cardiomyopathy (DCM). Fibrosis formation in the heart is one of the hallmarks in PLN patients, which compromises cardiac contractility and predisposes to arrhythmogenicity. Collagen type I is the most abundant type of collagen in the heart (85%). During continuous collagen synthesis propeptides, like procollagen type I carboxy-terminal propeptide (PICP) and during collagen breakdown, C-terminal telopeptide collagen type I (ICTP), are released into the circulation. Clinically, detection of fibrosis occurs via echo or MRI, however difficulties arise when patchy fibrosis has to be detected. Purpose: To investigate if PICP and ICTP levels in blood are useful predictive biomarkers for clinical outcome in PLN patients. Methods: 78 serum and EDTA blood samples were collected on the same day from ACM diagnosed (n = 12), DCM diagnosed (n = 14) or non-classified (n = 52) PLN patients. PICP levels were measured with an ELISA assay and ICTP with a RIA. Clinical data were subtracted two years around blood collection from Redcap, a Dutch database with medical records from PLN patients. Data were not normally distributed, so Spearman's correlation coefficient and Mann-Whitney test were used. Results: Gender, age and PICP/ICTP ratios were similarly distributed between the subgroups. First, we checked if clinical data subtracted two years around blood collection provided reliable results regarding clinical outcome. Patients who underwent clinical testing 5.5 weeks around blood collection revealed that clinical data were in line with the best-fitted line of the linear regression and therefore provide reliable results. Next, the potential correlation of fibrosis biomarkers with electrical parameters was assessed. Increased PICP/ICTP ratios suggest a higher collagen deposition. Although there was no correlation with prolonged QRS duration (Rs 0.13, n = 62, ns), subgroup analysis showed a significant weak correlation for non-classified patients (Rs 0.32, n = 38, p = 0.05). No significant correlation was found for ACM or DCM patients; however, groups were rather small. PICP/ICTP ratio was significantly higher in patients with T wave inversion and premature ventricular contractions (PVCs) during an exercise tolerance test. A weak inverted correlation was found with left ventricular ejection fraction and PICP/ICTP (Rs -0.28, n = 23, ns), while moderate correlations between the ratio and end diastolic volume, and end systolic volume exist (both Rs 0.40, n = 23, p = 0.06). Conclusion: High PICP/ICTP ratios correlate with clinical outcome in PLN patients, such as T wave inversion and PVCs. However, the size and heterogeneity of the patient group resulted in weak to moderate correlation coefficients and might therefore currently precludes to use PICP and ICTP levels as biomarker.